UPDATE OF THE INSTITUTIONAL METHODOLOGY OF ECONOMIC SECURITY RESEARCH IN THE CONDITIONS OF GLOBAL UNCERTAINTY - Berveno О.; Bronitsky О.; Berveno, S. (Municipal economy of cities. Series: «Economy science», 2023)
One of the global trends of the current stage of development of world civilization is economic security. This problem becomes more relevant for socio-economic systems that are in a state of transformation. Economic security is an integral element of the economic system and at the same time a part of a broader phenomenon - the security of social reproduction as a process richer in content. Economic security from the point of view of institutional economics is a product of habits and traditions that have developed in society. An important aspect of modern institutional research is the consideration of institutions not as separate sets of independent formations of multidirectional influence, but as an integral system that connects all institutions and directs them along a certain vector of development. It is thanks to the action of an extensive network of formal and informal institutions that stable foundations of socio-economic systems and a high level of certainty of socio-economic relations are formed. The criterion for the effectiveness of any new institution is its compliance with the interests and goals of society. The social assessment of the "public utility" of the institution, including the increase in the level of economic security, becomes the basis of trust in it. The system for ensuring economic security should conceptually be aimed not only at countering threats, but precisely at their prevention, at the formation of an institutional security environment. We are talking about internal mechanisms to support a stable, balanced, effective development of the economy, active preventive actions to ensure its margin of safety. This system of measures will be an important step forward on the path of institutional modernization. The mechanism for ensuring economic security is based on four political pillars: labor, benefits, protection and justice, therefore a set of institutional measures aimed at ensuring these parameters of the socio-economic system is the main guarantee of strengthening its security.